ISOLATION AND IDENTIFICATION OF ENTOMOPATHOGENIC ON CROSIDOLOMIA BINOTALIS [ZELLER] (LEPIDOPTERA : PHYRALIDAE) USING 16S rRNA GENE: ISOLATION AND IDENTIFICATION OF ENTOMOPATHOGENIC ON CROSIDOLOMIA BINOTALIS [ZELLER] (LEPIDOPTERA : PHYRALIDAE) USING 16S rRNA GENE - Carolin Manuahe (Indonesian Biodiversity Journal, 2021)
The aims of this reserach were to isolating and to identifying bacteria entomopathogenic on caterpillar pests in cabbage. The study was conducted in three phases. The first stage isolation of bacteria from cabbage caterpillar pests, the second stage of microscopic characterization of bacterial isolates and the third phase molecular identification of bacteria isolates using 16S RNA gene. The results were obtained five bacterial isolates of caterpillar pests in cabbage which 4 isolates shaped cocus, three isolates of gram positive and gram negative two isolates. All of isolates were able to degrade D-glucose. Isolates were translucent white color, white yellowish and brownish white. Generally isolates are not motile dan growth in the media to the surface. Results of DNA extraction and amplification of 16S RNA gene, showing the purity and concentration of DNA is good, confirmed by electrophoresis, amplicons formed band at 1500 bp according to the characteristics of the 16 S RNA gene